Microanatomical and biological aspects of bacterial associations in Tyrophagus putrescentiae (Acari: Acaridida) - Smrz, Jaroslav (Experimental & applied acarology, 2003)
The occurrence of bacterial colonies in the mesenchymal tissue of Tyrophagus putrescentiae Schrank was studied. One algal and two fungal species were offered as food. The experiment was analysed histologically and via transmission electron microscopy and plating of the mite homogenate. The dominant bacterium species, the bacterium population density in the mesenchyme, the location of bacterium groups between the internal organs and the ultrastructure were investigated. There were conspicuous differences between food types tested. On Penicillium, the highest population of bacteria in the mesenchymal tissue was correlated with the chitinase activity in mite homogenate. In this homogenate, Serratia marcescens was highly dominant among the other plated bacteria and it exhibited strong chitinolytic and trehalolytic activity.
Keywords: Choice Behavior; Acaridae; Microscopy, Electron; Eukaryota; Penicillium; krmivo pro zvířata; elektronová mikroskopie; Serratia marcescens; Alcaligenes faecalis; chitinasy; Chitinases; zvířata; Soil; Mesoderm; Animal Feed; preference v jídle; výběrové chování; Food Preferences; půda; mezoderm; Animals